EFEKTIVITAS MODEL PEMBELAJARAN BERBASIS PROYEK (PROJECT BASED LEARNING) TERHADAP KEAKTIFAN DAN KEMAMPUAN BERPIKIR KREATIF SISWA KELAS X SMA N 2 SEMARANG - Lilin Triani Putri; Harto Nuroso; Nur Khoiri (Jurnal Penelitian Pembelajaran Fisika, 2015)
This study aims to determine the effectiveness of project-based learning for the student’s activeness and creative thinking skills of students of Class X SMA N 2 Semarang. This research is experimental study with method of Quasi Experimental Non-equivalent Control Group Design. The data in this study is the result of creative thinking skills and student’s activeness. Data were analyzed using two-sample t test analysis. Research shows that 1) there is no difference in the early of ability between class that follows of project based learning process and the class that follows the cooperative learning (tresult = 0,4089 < ttable = 1,6663), 2) there is a difference between the results of creative thinking skills of  the students that follow of project-based learning (tresult = 10,12 >  ttable = 1.6663) and students who follow cooperative learning, 3) there is a difference between the student’s activeness of students that follows project-based learning (tresult = 49,56 > ttabel = 1,6663) and student who follow cooperative learning. Based on the results of this study, it can be concluded that the project-based learning is more effective than cooperative learning in improving learning results in the form of the student’s activeness and creative thinking skills.